Pemberdayaan Masyarakat Desa Melalui Pengembangan “ Soft Skill Pembuatan Krupuk Bawang” Di Kabupaten Lamongan Untuk Meningkatan Pendapatan Keluarga - Ardiansyah Ahsanul Hayat; Muhammad Qirom; Irma Indira; Darianto Darianto; Fitrotun Azizah (Pusat Riset dan Inovasi Nasional, 2021)
Many women in rural areas rely on working in the rice fields. Work in the fields is often only at the time of planting and at the time of harvest. Thus a lot of time is wasted on women. This community service activity is based on empowering rural communities through the development of soft skills in making onion crackers in Lamongan Regency to increase family income. The purpose of this activity is to empower women by providing skills that can increase family income